MAKING OF BOHEMIAN SKY DECORATION (FRINGE BOHEMIAN) - Ollivia Ollivia; Zulfahita Zulfahita; Nurul Anjani Diah Azizah; Nanda Nuryadi; Witri Witri (STKIP Singkawang, 2020)
For the student creativity program in this entrepreneurship class, we run a business program for hanging ornaments made of rope. We give this business the name of Making a Bohemian Ceiling Decoration (Fringe Bohemian). This Bohemian Ceiling Decoration is a craft made from rope. The rope used can be various as desired, such as rope, wool rope, plastic rope, etc. But we are here using the basic material of wool rope. This handicraft business aims to increase creativity and be innovative in entrepreneurship, especially for young entrepreneurs. The hanging decoration business from this rope is easy in the manufacturing process but it takes time and requires patience in making it and the materials needed to make this decoration easy to get. The form of our business is still in an individual stage only. We do not yet have official permission from the government, because this business is still new and is still trying to enter the business world. In the future, if this business can get extraordinary profits and have enough customers, then we will increase this business to be even bigger. Many factors need to be considered in order to advance this Bohemian Ceiling Decoration business. Important factors that must be considered in order to advance this business include choosing the right location, a good marketing strategy and determining affordable prices in the community. If all the factors above can be planned properly, it will be able to make this business grow well. For this reason, it is necessary to make a business plan as a reference in accelerating the business of making Bohemian Ceiling Decorations (Bohemian Fringe).